Comparison of OFF-State, HCI and BTI degradation in FDSOI Ω-gate NW-FETs. (August 2022) - Valdivieso, C.; Crespo-Yepes, A.; Miranda, R.; Bernal, D.; Martin-Martinez, J.; Rodriguez, R.; Nafria, M.
Abstract: In this work, the degradation of N-type FDSOI Ω-gate NW-FETs caused by OFF-State stress under different conditions has been experimentally studied and compared with the effects of positive/negative BTI and HCI aging. The experimental observations show that HCI and OFF-State are the most damaging aging mechanisms in these devices while N/PBTI produce negligible degradation. Moreover, for large enough stress conditions, OFF-State aging largely distorts the ID -VG curves of the transistor, leading to an almost linear dependence on VG .